What are the challenges in the vaccination of migrants in Norway from healthcare provider perspectives? A qualitative, phenomenological study. Issue 11 (24th November 2020) - Socha, Anna; Klein, Jörn
Abstract : Background: Migrant populations in the European Union (EU) suffer a disproportionate burden of infectious diseases and may be particularly vulnerable due to poor conditions in countries of origin or throughout transit to the host country. Given the rising level of migration into Europe, the vaccination of migrant populations has become a key priority, with European countries committing to equitably extending the benefits of vaccination to all. However, in Norway, little is known about the vaccination of migrant populations. Objective: The aim of this qualitative research study was to explore the process of vaccinating migrant populations in Norway and elucidate any challenges as perceived by healthcare providers. This involved exploring the challenges faced by healthcare providers in delivering vaccinations to migrants as well as potential barriers faced by migrants in accessing vaccinations in Norway, from the perspectives of healthcare providers. Methods: In June 2019, the authors conducted semi-structured interviews with seven healthcare providers who are involved in vaccinating migrants in South-Eastern and Western Norway. This included healthcare providers working in general practice, public health and infectious disease clinics, migrant health clinics, and local public health institutes. Results: An inductive, exploratory analysis identified key themes that were reviewed and analysed in light of existing literature. According to the informants, the Childhood Immunisation Programme is effective in including migrant children within the national vaccination schedule. However, gaps in vaccination appear to exist with regards to adult migrants as well as working migrants. There is currently no consistent or structured approach to vaccinating adult migrants in Norway, including no guidelines from governing bodies on how to organise vaccination to adult migrants in municipalities. Furthermore, reasons why adult vaccination is not prioritised were provided, such as tuberculosis screening and treatment taking precedence and the common assumption among healthcare providers that vaccinations are dealt with in childhood. Conclusion: The development of equitable immunisation programmes requires an understanding of the multifactorial barriers to immunisation, such as those posed by policies, structures and governance bodies, or lack thereof. It also entails understanding the administration of such policies and the perspectives of those who are responsible for the delivery of vaccination, namely healthcare providers. This qualitative research study demonstrated that challenges exist in the vaccination of migrants in Norway and that they are coherent with those experienced throughout the EU, principally the presence of gaps in vaccinating adult migrants, working migrants and internal EU migrants. This research provides direction for future investigations and highlights the need for the inclusion of migrant status in the Norwegian Immunisation Registry.